(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Every year, coronary heart disease (CHD) - the leading cause of death and disability in the world - becomes the cause of 9.4 million deaths. To date, extensive and substantial evidence of the connection between heart pathology and thyroid hypofunction has been accumulated. Subclinical hypothyroidism occurs in 15.8% of women and 6.7% of men with coronary heart disease. The thyroid gland is responsible for metabolism, as well as heart function and the peripheral vascular system. Thyroid dysfunction is associated with an increased risk of cardiovascular diseases, including heart failure and coronary heart disease, atrial fibrillation, due to impaired heart contractility, stroke volume, heart rate, peripheral vascular resistance, and electrical activity. Thyroid dysfunctions also alter several risk factors for cardiovascular diseases such as atherosclerosis, hypertension, and dyslipidemia, as well as cause stroke associated with atrial fibrillation. In the myocardium, these hormones stimulate both the diastolic relaxation of the myocardium and the systolic contraction of the myocardium, have a proangiogenic effect, and play an important role in maintaining the extracellular matrix. Thyroid hormones regulate the function of the heart mitochondria. Thyroid axis dysfunction worsens the bioenergetic status of the myocardium. Both clear and subclinical hypothyroidism are associated with a higher frequency of coronary events and an increased risk of heart failure progression.